ANALISIS PERKEMBANGAN SOSIOEMOSIONAL ANAK USIA SEKOLAH DASAR: TINJAUAN TEORI PSIKOSOSIAL ERIK ERIKSON - Setiawan, Sabrina Putri; Kuswandi, Alya Awwaliyatin; Nurhafidah, Leni; Puspa Restari, Mutiara; Rahmawati, Try; Mustikaati, Wina (Pusat Penelitian dan Pengabdian kepada Masyarakat STKIP Citra Bakti, 2026)
Primary school age is a critical period for character formation, yet modern education often faces a dilemma between high academic demands and children's mental health needs. This study aims to map the factors supporting industry and triggering inferiority in elementary school students by integrating Erik Erikson's psychosocial theory with contemporary educational dynamics, including the Kurikulum Merdeka. This research uses a qualitative approach, combining a Literature Review of academic databases from 2021–2026 and field studies through in-depth interviews with parents. Data were analyzed using the Miles and Huberman model, encompassing reduction, systematic display, and conclusion drawing. The findings indicate that children's confidence and competence develop optimally through collaborative, flexible, and process-oriented learning, supported by emotional scaffolding from teachers and parents. Conversely, excessive academic pressure (parental pressure) and digital social comparison especially through platforms like TikTok significantly trigger inferiority and academic anxiety. The synergy between supportive school environments and adaptive parenting is essential to mitigate these digital and academic stressors to ensure balanced psychosocial development.